Acupuncture therapy for radiotherapy-induced adverse effect: A systematic review and network meta-analysis - Wu, Tong; Fu, Chengwei; Deng, Yiran; Huang, Wanping; Wang, Jieyu; Jiao, Yang (Frontiers in Public Health, 2022)
Objective To evaluate the efficacy of different acupuncture therapies for radiotherapy-induced adverse effects (RIAEs) and find out the optimal scheme. Methods Eligible randomized controlled trials (RCTs) were collected from inception to June 2020 from 9 bibliographic databases. The risk of bias evaluation of the analyzed literature was carried out using the Cochrane risk-of-bias tool. Network meta-analysis was mainly performed using STATA 14.2 and OpenBUGS 3.2.3 by figuring out the network diagrams, league figures, and SUCRA values. Results A total of 41 studies with 3,011 participants reported data suitable for network meta-analysis. There was a low to moderate risk of bias in twenty of the articles. ST36 was the most widely prescribed acupoint. Based on network meta-analysis, four outcome indicators were described, namely, acupuncture + medication ranked first in treating radiation enteritis, moxibustion + medication ranked first in preventing radiotherapy-induced leukopenia, acupuncture + medication ranked first in preventing radioactive oral mucositis, and acupuncture ranked first in improving the stimulated salivary flow rate of radioactive xerostomia. Conclusion The findings of the network meta-analysis manifested that acupuncture therapy combined with medication has superiority in most RIAEs, both reducing incidence and relieving symptoms. However, high-quality studies are still needed to provide conclusive evidence. Systematic review registration https://inplasy.com/inplasy-2020-7-0054/, identifier: INPLASY202070054.